Pembelajaran Sains dengan Konteks Physical Science pada Anak Usia Dini - Miftahurrohmah, Linda; Nurul Khotimah; Ruqoyyah Fitri (JOURNAL OF EDUCATION FOR ALL, 2024)
Science is a process og gaining knowledge related to activities looking for natural phenomena or fact through natural activities or research by observation using the scope of physical science. Physical science is a learning process that provides direct experience for children to interact with scientific materials and encourages children’s initiative to explore these phycical materials. Physical science is seen as a process so that in learning it must consider learning strategies or methods, one of which is through demonstration and practical activities. This research uses a qualitative type of research with research using the literature study method. The results of the research explain the importance of science and science activities that can be carried out with children by introducing God’s creation and all of nature using experiments that are safe for children.